2000
DOI: 10.1038/sj.bjp.0703407
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in the vasculature: mechanisms and functional importance

Abstract: Apoptotic death has now been recognized in a number of common and threatening vascular diseases, including atherosclerosis. Interest in apoptosis research relates to the fact that apoptosis, in contrast to oncosis, is a highly regulated process of cell death which raises the hope for the development of speci®c therapeutic strategies to alter disease progression. This review summarizes the mechanisms involved in vascular endothelial and smooth muscle cell survival/apoptosis, and the potential roles of apoptotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
217
0
11

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 307 publications
(230 citation statements)
references
References 154 publications
(177 reference statements)
2
217
0
11
Order By: Relevance
“…Several in vitro studies have demonstrated that a variety of stimuli can induce programmed cell death (apoptosis) in endothelial cells (1,2), and anomalous endothelial cell apoptosis has been considered a common feature in numerous cardiovascular diseases such as atherosclerosis, hypertension, and diabetes (3)(4)(5)(6)(7)(8). Endothelial cell death leads to vascular leak and exposes the flowing bloodstream to the potently thrombogenic subendothelial matrix.…”
mentioning
confidence: 99%
“…Several in vitro studies have demonstrated that a variety of stimuli can induce programmed cell death (apoptosis) in endothelial cells (1,2), and anomalous endothelial cell apoptosis has been considered a common feature in numerous cardiovascular diseases such as atherosclerosis, hypertension, and diabetes (3)(4)(5)(6)(7)(8). Endothelial cell death leads to vascular leak and exposes the flowing bloodstream to the potently thrombogenic subendothelial matrix.…”
mentioning
confidence: 99%
“…It is well-established that apoptosis can be induced by internal signals, such as cytochrome C and apoptosis-inducing factors released from mitochondria, and that it is commonly associated with decreases in mitochondrial membrane potential and ATP production (14 -16). In addition, such factors as caspases, ceramide, and oxidative stress have been implicated in its causation, whereas other factors, including shear stress, IGF-I, insulin, and Akt activation, have been shown to be antiapoptotic (17)(18)(19)(20)(21). Despite this, the metabolic mechanism(s) by which hyperglycemia initiates apoptosis in endothelium is incompletely understood.…”
mentioning
confidence: 98%
“…VSMCs, the main structure of artery medium layer, also play a significant role on the formation of advanced stage of atherosclerosis. Apoptosis of VSMCs is harmful to the stability of atherosclerosis plaque [42]. Therefore, maintenance of VSMCs has potential to delay the progression of atherosclerosis [31].…”
Section: Let-7g and Apoptosismentioning
confidence: 99%